2012
DOI: 10.5603/17845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the specificity and selectivity of anti-EpCAM antibodies in breast cancer cell lines

Abstract: Abstract:The epithelial cell adhesion molecule (EpCAM) is a membrane glycoprotein that is expressed in most normal human epithelia and overexpressed in most carcinomas. This molecule is responsible for cell-to-cell adhesion and additionally participates in signalling, cell migration, proliferation and differentiation. Therefore, EpCAM has been the target of immunotherapy in clinical trials of several solid tumours. It has been found to play an important role in the detection and isolation of circulating tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…48 Studies have shown that the expression of EpCAM depends on many factors, such as tumor type, disease stage, tumor microenvironment and host anti-tumor immunity. 49 In this study, we incorporated an EpCAM peptide into the phi29 connector channel. A linker with 6-glycines was included between the gp-10 connector and the EpCAM peptide probe to provide end flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…48 Studies have shown that the expression of EpCAM depends on many factors, such as tumor type, disease stage, tumor microenvironment and host anti-tumor immunity. 49 In this study, we incorporated an EpCAM peptide into the phi29 connector channel. A linker with 6-glycines was included between the gp-10 connector and the EpCAM peptide probe to provide end flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prepared glass surfaces were used for specific monoclonal antibody immobilization enabling biomolecule capturing. [20] Prior to dendron modification, the glass slides were pre-cleaned with a mixture of hydrochloric acid and methanol to remove any impurities. The glass surface was highly hydrophilic with a contact angle of less than 10°.…”
Section: Resultsmentioning
confidence: 99%
“…The recent reports have shown how variable the EpCAM expression can be, and, in conclusion, how cocktail of antibodies is eligible [15][16][17][18]. A combination of antibodies bound to the beads would enable the capturing of cancer cells, which do not necessarily express EpCAM as used in the Adnatest™ protocols.…”
Section: Discussionmentioning
confidence: 99%